MMT/MMIRS spectroscopy of z = 1.3 - 2.4 extreme [O iii] emitters: implications for galaxies in the reionization era. Issue 2 (12th August 2019) - Tang, Mengtao; Stark, Daniel P; Chevallard, Jacopo; Charlot, Stéphane
ABSTRACT: Galaxies in the reionization era have been shown to have prominent [O iii ] + H β emission. Little is known about the gas conditions and radiation field of this population, making it challenging to interpret the spectra emerging at z ≳ 6. Motivated by this shortcoming, we have initiated a large MMT spectroscopic survey identifying rest-frame optical emission lines in 227 intense [O iii ] emitting galaxies at 1.3 < z < 2.4. This sample complements the MOSDEF and KBSS surveys, extending to much lower stellar masses ($10^7\!-\!10^8 \, M_\odot$ ) and larger specific star formation rates (5–300 Gyr −1 ), providing a window on galaxies directly following a burst or recent upturn in star formation. The hydrogen ionizing production efficiency (ξion ) is found to increase with the [O iii ] equivalent width (EW), in a manner similar to that found in local galaxies. We describe how this relationship helps explain the anomalous success rate in identifying Ly α emission in z ≳ 7 galaxies with strong [O iii ] + H β emission. We probe the impact of the intense radiation field on the ISM using O32 and Ne3O2, two ionization-sensitive indices. Both are found to scale with the [O iii ] EW, revealing extreme ionization conditions not commonly seen in older and more massive galaxies. In the most intense line emitters, the indices have very large average values (O32 = 9.1, Ne3O2 = 0.5) that have been shown to be linked to ionizing photon escape. We discuss implications for the nature of galaxies most likely to have O32 values associated with significant LyC escape. Finally we consider the optimal strategy for JWST spectroscopic investigations of galaxies at z ≳ 10 where the strongest rest-frame optical lines are no longer visible with NIRSpec.